Baudelaire & the English tradition - Clements, Patricia (Princeton legacy library, 1985)
This study of Baudelaire and English modernism observes his protean influence on poets from Swinburne, who wrote the first English review of Les Fleurs du Mai, to T.S. Eliot. Documenting Baudelaire's impact on Swinburne, Pater, Wilde, Arthur Symons, Aldous Huxley, Edith and Osbert Sitwell, D.H. Lawrence, the Imagists, John Middleton Murry, Eliot, and others, Patricia Clements describes the Baudelaire who is the creation of the English poets and identifies some major lines in the development of modernism in English literature. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.